Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.3389/fmicb.2015.00150
|View full text |Cite
|
Sign up to set email alerts
|

Formate hydrogen lyase mediates stationary-phase deacidification and increases survival during sugar fermentation in acetoin-producing enterobacteria

Abstract: Two fermentation types exist in the Enterobacteriaceae family. Mixed-acid fermenters produce substantial amounts of lactate, formate, acetate, and succinate, resulting in lethal medium acidification. On the other hand, 2,3-butanediol fermenters switch to the production of the neutral compounds acetoin and 2,3-butanediol and even deacidify the environment after an initial acidification phase, thereby avoiding cell death. We equipped three mixed-acid fermenters (Salmonella Typhimurium, S. Enteritidis and Shigell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…The deacidification of the medium requires fhlA and hyf. It has been known that formate, a product of mixed-acid fermentation, can be converted to H 2 and CO 2 by the FHL complex, in a process consuming protons and resulting in medium deacidification, thereby increasing bacterial survival 17 . We hypothesized that uropathogenic P. mirabilis could use the FHL system to consume protons, leading to deacidification of the environment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The deacidification of the medium requires fhlA and hyf. It has been known that formate, a product of mixed-acid fermentation, can be converted to H 2 and CO 2 by the FHL complex, in a process consuming protons and resulting in medium deacidification, thereby increasing bacterial survival 17 . We hypothesized that uropathogenic P. mirabilis could use the FHL system to consume protons, leading to deacidification of the environment.…”
Section: Resultsmentioning
confidence: 99%
“…medium deacidification during mix acid fermentation 17 and acid resistance in the anaerobic environment 18 . In addition, hydrogenases of FHL might play a role in virulence by neutralizing hydroxyl free radicals (OH•), providing energy and maintaining acid-base homeostasis 19 .…”
mentioning
confidence: 99%
“…The apparent primary role of the enzyme complexes is to dissipate reductant and detoxify formate during persistence under anoxia. However, three independent studies have indicated that FHL complexes are also critical for acid tolerance in E. coli and S. Typhimurium (79,84,322). These complexes mediate the net consumption of protons from the cytosol (HCOO Ϫ ϩ H ϩ ¡ CO 2 ϩ H 2 ) and, hence, may provide a simple but elegant mechanism to regulate internal pH.…”
Section: H 2 Production In Pathogens Bacteriamentioning
confidence: 99%
“…When the pH in the periplasmic space of the E. coli cell becomes too acidic, FocA working together with FHL-1 alleviates pH stress [8, 23, 64, 78–80]. In this situation, the proton associated with formic acid might not be relayed back to H209, but instead would be translocated directly into the cytoplasm along with the anion (); this might result from the H209/T91 proton-relay system being overwhelmed by the high concentration of formic acid, with FocA adopting an inwardly directed channel-like function (see ).…”
Section: Role Of Foca In Helping Prevent Acidification Of the Peripla...mentioning
confidence: 99%